2016
DOI: 10.1021/acs.jmedchem.6b00184
|View full text |Cite
|
Sign up to set email alerts
|

H2S-Donating Doxorubicins May Overcome Cardiotoxicity and Multidrug Resistance

Abstract: Doxorubicin (DOXO) is one of the most effective antineoplastic agents in clinical practice. Its use is limited by acute and chronic side effects, in particular by its cardiotoxicity and by the rapid development of resistance to it. As part of a program aimed at developing new DOXO derivatives endowed with reduced cardiotoxicity, and active against DOXO-resistant tumor cells, a series of H2S-releasing DOXOs (H2S-DOXOs) were obtained by combining DOXO with appropriate H2S donor substructures. The resulting compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 49 publications
3
61
0
Order By: Relevance
“…The ADT-OH H 2 S-releasing group has also been used to derivatize a variety of additional clinically used drugs including the N-methyl-D-aspartate receptor antagonists memantin and amantadine (Marutani et al, 2014), the antistroke compound 3-n-butylphthalide Yin et al, 2016), doxorubicin (Chegaev et al, 2016), olenoic acid (Xu et al, 2016a), glycyrrhetic acid (Song et al, 2016), nicotinic acid (Sun et al, 2016b), naproxen, as an amide derivative resistant to hydrolysis (Hammers et al, 2016), valproic acid (Hammers et al, 2016), losartan (Martelli et al, 2012), and the Chinese traditional compound Danshensu [b-(3, 4-dihydroxyphenyl)lactic acid] (Yan et al, 2017). Most of these compounds remain to be further characterized with respect to their pharmacological effects in vitro and in vivo.…”
Section: Combined (Or Hybrid) Molecules: H 2 S-donating Derivamentioning
confidence: 99%
“…The ADT-OH H 2 S-releasing group has also been used to derivatize a variety of additional clinically used drugs including the N-methyl-D-aspartate receptor antagonists memantin and amantadine (Marutani et al, 2014), the antistroke compound 3-n-butylphthalide Yin et al, 2016), doxorubicin (Chegaev et al, 2016), olenoic acid (Xu et al, 2016a), glycyrrhetic acid (Song et al, 2016), nicotinic acid (Sun et al, 2016b), naproxen, as an amide derivative resistant to hydrolysis (Hammers et al, 2016), valproic acid (Hammers et al, 2016), losartan (Martelli et al, 2012), and the Chinese traditional compound Danshensu [b-(3, 4-dihydroxyphenyl)lactic acid] (Yan et al, 2017). Most of these compounds remain to be further characterized with respect to their pharmacological effects in vitro and in vivo.…”
Section: Combined (Or Hybrid) Molecules: H 2 S-donating Derivamentioning
confidence: 99%
“…demonstrated that exogenous H 2 S (NaHS) attenuates doxorubicin (DOX) induced cytotoxic effects in H9c2 cardiac cells through the PI3K/Akt/FoxO3a pathway. During the same period, Chegaev et al . reported a series of H 2 S‐releasing doxorubicin analogs (H 2 S‐DOXs) by combining DOX with an appropriate H 2 S donor substructure (Fig.…”
Section: Hydrogen Sulfide Prodrugs and Delivery Approachesmentioning
confidence: 99%
“…Moreover, Chegaev et al reported a series of new doxorubicin derivatives (H 2 S-DOXOs), which combined doxorubicin with appropriate H 2 S donor substructures. These H 2 S-releasing doxorubicins were safe and effective at 5 μM concentration on H9c2 cells, without any toxicity (Chegaev et al, 2016 ). They observed that a few compounds even could trigger high activity on the cancer cells and might be used to take the place of naked doxorubicin in the future.…”
Section: Clinical Prospect Of H 2 S As Cardiac Promentioning
confidence: 99%